Comparative effectiveness of acid and water degumming methods in Crude Palm Oil (CPO) pretreatment - Sumarna, Denny; Purba, Nova Solina (Journal of Tropical AgriFood, 2026)
Crude Palm Oil (CPO) is the primary raw material in the cooking oil industry; it must be refined to improve its quality and stability. Degumming is a critical pretreatment step in CPO refining, as it removes phospholipids that can affect the oil quality. This study aimed to evaluate the effects of two degumming methods, acid degumming and water degumming, on various quality parameters of CPO, including moisture content, free fatty acids (FFA), tocopherols, beta-carotene, and peroxide levels. The results showed that both degumming methods significantly reduced the FFA content and peroxide number. Acid and water degumming were effective in lowering the FFA content and removing impurities from crude palm oil (CPO). They reduced the FFA level by 79.8-80.7% and by 15.9-17.3% for the peroxide number. Although reductions in α-tocopherol were observed, they remained acceptable and did not affect nutritional value.